The effects of active play interventions on children’s fundamental movement skills: a systematic review - Xinmiao Zhang; Changhao Tang; Miao Geng; Kai Li; Cong Liu; Yujun Cai (BMC Pediatrics)
Abstract Background Many countries worldwide face the problem of underdeveloped fundamental movement skills (FMS) in children. Active play (AP) holds significant potential for enhancing children’s FMS based on its free-choice and unstructured nature, as well as its ease of implementation and dissemination. Therefore, the primary objective of this systematic review was to determine the effects of AP interventions on FMS in typically developing children. Methods A systematic literature search was conducted in six electronic databases, Web of Science, PubMed, Embase, Scopus, China National Knowledge Infrastructure (CNKI), and Wan Fang Data, from database inception to May 30, 2024. The main inclusion criteria for literature screening included the intervention modality being AP, the outcome indicator as FMS, and the intervention being for typically developing children. Information on countries and regions, study types, experimental designs, sample characteristics, measurement methods, and intervention effects of the included literature were extracted for the included literature. To assess the risk of bias in the literature, the RoB2.0 tool was used for RCTs, while the ROBINS-I 2.0 tool was applied to non-RCTs. Result Of the 3,672 articles retrieved, 9 studies were ultimately included in this review. The risk of bias assessment identified 3 studies as having a low risk of bias and 6 as having a moderate risk. The AP interventions in these 9 studies exhibited varying characteristics, with individual intervention durations ranging from 45 to 60 min, intervention frequencies ranging from once a week to four times per week, and intervention periods spanning from 4 weeks to 6 months. FMS were assessed using the Test of Gross Motor Development-2 (TGMD-2), the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP), the Peabody Development Motor Scales-2 (PDMS-2), and the Movement Assessment Battery for Children (MABC). Regarding the effects of AP interventions on children’s FMS, seven studies reported a significant effect, while two others reported no significant effect. Conclusion Although the results of the included studies are inconsistent, AP interventions generally demonstrate a positive effect on FMS in typically developing children. To better understand the potential of AP in developing FMS in children, high-quality AP interventions and more in-depth studies across diverse populations, settings, and timeframes are needed. Additionally, greater clarity is needed regarding the components of AP interventions and their quantitative relationships with FMS efficacy.